Stress Coping Strategies among Teachers at Madrasah Ibtidaiyah Al-Qomar Nganjuk during the Covid-19 Pandemic - Risma Udhia Fitria; Nafikadini, Iken; Erwin Nur Rif'ah (Jurnal Promkes: The Indonesian Journal of Health Promotion and Health Education, 2023)
Background: COVID-19 pandemic has become a new source of stress among teachers. Education was originally carried out directly and has now changed to network-based (online), so it is not uncommon for teachers to experience work stress. Objective: This study aims to analyze stress coping among teachers at MI Al-Qomar Nganjuk during the COVID-19 pandemic. Methods: This study used qualitative research with a case study. There were 9 informants consisting of 1 key informant, 5 main informants, and 3 additional informants. Data collection techniques are in-depth interviews, observation, and documentation. Data analysis used thematic content analysis. The credibility test used triangulation of techniques and sources. Results: The results of the study state that the source of stress among teachers who come from stressors is task demands during the pandemic such as teachers being required to create learning innovations, achievement of student learning outcomes that have not been running optimally and increasing task demands. There are two stress coping used by the informants, problem-focused coping and emotional-focused coping. As many as 4 informants mostly use problem-focused coping with aspects of planful-focused coping and seeking social support. In addition, all key informants also use emotional-focused coping, which mostly uses positive reappraisal aspects. Conclusion: The informants are positive, as indicated by the condition of the informants after using the two copings, they feel better and have a positive impact on the stress they experience.